2016
DOI: 10.1038/srep31177
|View full text |Cite
|
Sign up to set email alerts
|

A new survivin tracer tracks, delocalizes and captures endogenous survivin at different subcellular locations and in distinct organelles

Abstract: Survivin, the smallest member of the inhibitor of apoptosis protein family, plays a central role during mitosis and exerts a cytoprotective function. Survivin is highly expressed in most cancer types and contributes to multiple facets of carcinogenesis. The molecular mechanisms underlying its highly diverse functions need to be extensively explored, which is crucial for rational design of future personalized therapeutics. In this study, we have generated an alpaca survivin nanobody (SVVNb8) that binds with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Our approach and complementary developments in other labs (Beghein et al, 2016, Harmansa et al, 2017, Herce et al, 2013, Steels et al, 2018 open up new avenues for analyzing signaling pathways in primary and motile cilia, as demonstrated by the application of the cilia-targeted nanobody in zebrafish, and beyond that in many other subcellular domains in vitro and in vivo. The nanobody-based targeting approach conveys high specificity through a strong interaction with its binding partner (K d ~ 1 nM), which is a prerequisite for subcellular targeting and binding of endogenously expressed proteins in vitro and in vivo (Beghein & Gettemans, 2017, Van Overbeke, Wongsantichon et al, 2015.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our approach and complementary developments in other labs (Beghein et al, 2016, Harmansa et al, 2017, Herce et al, 2013, Steels et al, 2018 open up new avenues for analyzing signaling pathways in primary and motile cilia, as demonstrated by the application of the cilia-targeted nanobody in zebrafish, and beyond that in many other subcellular domains in vitro and in vivo. The nanobody-based targeting approach conveys high specificity through a strong interaction with its binding partner (K d ~ 1 nM), which is a prerequisite for subcellular targeting and binding of endogenously expressed proteins in vitro and in vivo (Beghein & Gettemans, 2017, Van Overbeke, Wongsantichon et al, 2015.…”
Section: Discussionmentioning
confidence: 97%
“…Harmansa et al have mislocalized transmembrane proteins, cytosolic proteins, and morphogens in Drosophila to study the role of correct protein localization for development in vivo (Harmansa et al, 2017). Targeting to organelles using nanobodies has also been achieved for two specific proteins, p53 and survivin (Beghein, Van Audenhove et al, 2016, Steels, Verhelle et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…They have broad utility as biomedical research reagents, diagnostics and therapeutics. nAbs are ideally suited for use as intracellular antibodies (intrabodies) in living cells (Beghein et al, 2016;Bertier et al, 2017;Lafaye et al, 2009;Schumacher et al, 2018;Staus et al, 2014;Van Audenhove and Gettemans, 2016), as they fold efficiently and remain stable under a wide range of conditions, including the reducing cytoplasmic environment (Boldicke et al, 2005;Gahrtz and Conrad, 2009;Goenaga et al, 2007;Lynch et al, 2008). In addition to their potential utility as intrabodies, nAbs also have advantages as immunolabeling reagents, as their small size (≈1/10 of conventional IgG antibodies) improves penetration of the cell or tissue samples (Fang et al, 2018;Perruchini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This had not yet been investigated. Also, transport of survivin in the peroxisomes (PST-1 tag) was demonstrated [72]. Since interaction between the nanobody and survivin apparently did not perturb survivin functionality, the tagged nanobody is a perfect research tool for further elucidating survivin biology.…”
mentioning
confidence: 99%
“…Considering that the paratope of the nanobody is located at its N-terminal end, it is safer to fuse the tag at the C-terminal end of the nanobody. Otherwise, a substantial risk at disturbing antigen binding exists [2], although there are examples where a long tag is added to the nanobody N-terminus without disturbing its functionality [72]. Beghein et al elegantly demonstrated how effectively nanobodies can delocalize their target protein to a variety of subcellular organelles.…”
mentioning
confidence: 99%